2018
DOI: 10.1002/aelm.201800355
|View full text |Cite
|
Sign up to set email alerts
|

Highly Improved Switching Properties in Flexible Aluminum Oxide Resistive Memories Based on a Multilayer Device Structure

Abstract: Multilayer aluminum oxide (Al2O3) resistive memory devices, exhibiting robust switching properties fabricated on a flexible polyethylene naphthalate substrate using only physical vapor deposition methods at room temperature, are reported here. Improved reliability and robust switching properties of the multilayer Al2O3 memory devices are observed compared to those of the single‐layer devices, with the assistance of a guide filament formed in the bottom Al2O3 resistive layer. The multilayer Al2O3 resistive memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The most straightforward approach to obtain flexible memristive arrays is directly depositing inorganic materials onto flexible substrates via thin-film fabrication processes, such as evaporation and sputtering. Until now, a large number of inorganic materials, such as AlO x (Lee et al, 2017;Jang et al, 2018b), SiO x (Yoon et al, 2018), WO x (Lin et al, 2018), and HfAlO x (Wang et al, 2020d;Wang et al, 2021c), have been fabricated as flexible resistive switching dielectrics by using this approach. For instance, J. Yoon et al reported a 8 × 8 flexible SiO x -based one diode-one resistor (1D-1R) memristive crossbar array on a plastic substrate by employing physical vapor deposition (PVD) technology (Yoon et al, 2018).…”
Section: Flexible Inorganic Memristive Arraysmentioning
confidence: 99%
“…The most straightforward approach to obtain flexible memristive arrays is directly depositing inorganic materials onto flexible substrates via thin-film fabrication processes, such as evaporation and sputtering. Until now, a large number of inorganic materials, such as AlO x (Lee et al, 2017;Jang et al, 2018b), SiO x (Yoon et al, 2018), WO x (Lin et al, 2018), and HfAlO x (Wang et al, 2020d;Wang et al, 2021c), have been fabricated as flexible resistive switching dielectrics by using this approach. For instance, J. Yoon et al reported a 8 × 8 flexible SiO x -based one diode-one resistor (1D-1R) memristive crossbar array on a plastic substrate by employing physical vapor deposition (PVD) technology (Yoon et al, 2018).…”
Section: Flexible Inorganic Memristive Arraysmentioning
confidence: 99%
“…As a matter of fact, in addition to utilizing binary‐oxides functional layer to fabricate resistive switching memory, there were a large amount of works reported novel assembly of diverse binary‐oxide with multilayer nanostructures for improving the performance of binary‐oxide based ReRAM devices . The majority of binary‐oxides were employed as the functional layers.…”
Section: Resistive Switching Memorymentioning
confidence: 99%
“…A RRAM cell generally is composed of a metal electrode/insulator/metal (MIM) electrode sandwiched structure [3]. Currently, binary metal oxides such as Al 2 O 3 [4][5][6], TiO 2 [7][8][9], HfO x [10], TaO x [11,12], MoO 3 [13], ZnO [14] or NiO [15] have been mainstreaming insulators for RRAM due to their simple structure, controlled composition and compatibility with complementary metal-oxide-semiconductor(CMOS) processes. However, the problems of binary metal oxide-based RRAMs are obvious, such as more sophisticated methods or using expensive equipment, balance of performance parameters of RRAMs which hinder the realization of their practical applications.…”
Section: Introductionmentioning
confidence: 99%